The Effect of Cirprofloxacin (CPX) on the Histological Structure of Albino Rabbit Ovary - Jabbar Ebadi Mohammad (Journal of Global Pharma Technology, 2018)
The study was conducted in the Animal House of the Department of Biology / Faculty of Education for Women / University of Kufa from October 2016 to May 2017. The study included 72 lab albino rabbit eggs of the type Oryetolagus cuniculus.L divided into four groups of 18 rabbits. They were injected with ciprofloxacin at a concentration of 1 mg / kg bw. The bacteria dose was (1 mg / kg bw) for a week, two weeks, and four weeks respectively. After infusion and injections of all experiment animals, they were sacrificed and dissected for the histological study, which included the female reproductive system. As well, blood samples were taken for blood and chemical indices. The results of the statistical analysis at the probability level (P <0.05) showed that the antibiotic (ciprofloxacin) caused changes in weight by significant decrease (P <0.05) in the total body weight and ovarian weight in females. The results of the statistical analysis of the study showed that the single therapeutic injection of ciprofloxacin and bacterial injection were different in their effect on some blood parameters. The groups of drug and bacterial treatment did not show changes in the first and second weeks, while there was a significant decrease and below the probability level (P <0.05) in the fourth group by number of WBCs, RBCs and hemoglobin (Hb) compared to the control group. Under optical microscopy, the histological study of tissue sections showed patho-histological changes of different intensity and appearance in the female ovaries between the drug and bacteria compared to the control group. The results of the microscopic examination showed clear effects on ovarian tissue structure in females compared with control group.Keywords: Ciprofloxacin; Biochemical tests; Biology; Histopathology; Ovary ; Albino female rabbits.